Factors Affecting Behavioral Intention of Millennial Generation Using Mobile Delivery Order Services in Digital Era Revolution - Hera Febria Mavilinda; Yulia Hamdaini Putri; Akhmad Nazaruddin (University of Merdeka Malang, 2023)
The purpose of this research is to analyze the factors that can influence the behavioral intention of the millennial generation towards the use of mobile delivery order (MDO) in food delivery services. Questionnaires were distributed to 218 respondents who are millennials and have used the mobile delivery order services. The sampling technique uses non-probability random sampling methods. This research is a quantitative research that using Structural Equation Modeling (SEM) analysis which is operated by Analysis of Moment Structure (AMOS) program. The results showed that the variables of perceived usefulness, time saving orientation and non-pharmaceutical intervention are factors that can influence the behavioral intention of the millennial generation for using MDO in food delivery services. Meanwhile, the perceived ease of use has no significant effect on the behavioral intention of the millennial generation for using MDO.